Study of Fingerprints in Relation to Dental Caries (Indian Journal of Forensic Medicine & Toxicology, 2020)
Fingerprints of 40 individuals of age group 4-18 years were sampled from Agyaram Kherbari L.P. School, D. L. P School and J.N. M. E school (Dhubri District) to study the pattern of fingerprints and their relation with dental caries as they may be associated with the disease and serve as a predictor for early detection of it. Analysis was carried out in the affected individuals and it was found that the per centage of ulnar loop is highest (23.75%) in females and also in males (19.7%) and per centage of lateral loop is lowest (1.25% and 1.24%), whereas the control had more per centage of ulnar loop in both males and females. The study shows an association of dermatoglyphic pattern of fingerprints and prevalence of dental caries.